Imagined Romes : the ancient city and its stories in Middle English poetry - Benson, C. David (The Pennsylvania State University Press, 2019)
"A study of ancient Rome as a prominent topic in the works of Middle English poets. Discusses how each of these poets conceives of ancient Rome and Romans, both pagan and Christian, and why it matters to their work. Includes the works of Gower, Chaucer, Langland, and Lydgate"--Provided by publisher